PMS1077 sensitizes TNF-α induced apoptosis in human prostate cancer cells by blocking NF-κB signaling pathway. - Jie Shi (Public Library of Science (PLoS), 2013)
Our previous studies have demonstrated that PMS1077, a platelet-activating factor (PAF) antagonist, could induce apoptosis of Raji cells. However, the mechanism of action has not yet been determined. The nuclear transcription factor-kappa B (NF-κB) signaling pathway plays a critical role in tumor cell survival, proliferation, invasion, metastasis, and angiogenesis, so we determined the effects of PMS1077 and its structural analogs on tumor necrosis factor-α (TNF-α) induced activation of NF-κB signaling. In this study, we found that PMS1077 inhibited TNF-α induced expression of the NF-κB regulated reporter gene in a dose dependent manner. Western blot assay indicated that PMS1077 suppressed the TNF-α induced inhibitor of κB-α (IκB-α) phosphorylation, IκB-α degradation, and p65 phosphorylation. PMS1077 consistently blocked TNF-α induced p65 nuclear translocation as demonstrated in the immunofluorescence assay used. Docking studies by molecular modeling predicted that PMS1077 might interact directly with the IκB kinase-β (IKK-β) subunit. These results suggested that PMS1077 might suppress the activation of NF-κB by targeting IKK-β involved in the NF-κB signaling pathway. Finally, we showed that PMS1077 sensitized cells to TNF-α induced apoptosis by suppressing the expression of NF-κB regulated anti-apoptotic genes. Our results reveal a novel function of PMS1077 on the NF-κB signaling pathway and imply that PMS1077 can be considered as an anti-tumor lead compound.